MONEY LAUNDERING USING FINANCIAL TECHNOLOGY THROUGH E-COMMERCE TRANSACTIONS (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2022)
The rapid development of technology today makes all activities in human life can be carried out easily. One of them is to make payments through an application in a smartphone. Payment with these technological innovations or in other words, technology-based financial services are commonly referred to as fintech. Fintech is here to facilitate the process of financial transactions but also has a bad impact on the economic sector, one of which is money laundering. Money laundering activities can currently be carried out through fintech. The illegal act of money laundering through fintech is increasingly difficult to know who is behind the scenes. The purpose of this study is to make an improvement in legislation in the field of financial technology, which until now is still nil. This research is carried out through a normative approach using a statutory approach and a conceptual approach. The result of this study is to provide a new policy on financial technology, especially in money laundering activities carried out on the use of e-ecommerce transactions where currently there is none.